Earnouts in mergers and acquisitions: a systematic literature review of a contingent payment mechanism - Niklas Dahlen (Management Review Quarterly, 2024)
Defining the deal value in mergers and acquisitions is inherently complex and often constitutes an inflection point for the parties involved. By paying part of the deal value at a later stage according to predefined goals, earnouts are intended to alleviate information asymmetries and help bridge valuation differences. Despite their wide application in practice, research on earnouts remains fragmented. This study presents the first systematic literature review of earnouts, mapping the scattered research landscape by analyzing 64 papers published between 1970 and 2023. The review categorizes the body of earnout research into three distinct streams: the motives for employing earnouts, their implications, and the nuances of their contractual arrangements. Based on this synthesis, research gaps are identified that present a comprehensive road map for future research. This study enables investors to employ earnouts more successfully and guides scholars to pursue further earnout research based on its holistic overview.
Keywords: G34; G32; G13; D82; 650; Earnout; Mergers and acquisitions; Contingent payments; Performance commitment; Contingent claims; Information asymmetries; Systematic literature review